Elucidating the role of Cavin1 in drug-induced long QT syndrome (diLQTS). (14th October 2021) - Al Sayed, Z R; Pereira, C; Jouve, C; Hulot, J.-S
Abstract: Introduction: Several drugs can induce QT prolongation by altering cardiac ion currents, notably IKr. The cardiotoxic response to a drug is however extremely variable between individuals, ranging from no impact to life-threatening ventricular arrhythmias. The molecular mechanisms underlying this variability remain unclear. Previously, we reported higher expression levels of Cavin1, an essential protein for caveolae formation, in cardiomyocytes (CM) derived from patients with high susceptibility to develop sotalol-induced long QT. Purpose: We aimed to explore whether Cavin1 could sway the cardiac repolarization response to drugs. Method: We used induced pluripotent stem cells-derived CM (iPS-CM) from two subjects with the highest sensitivity (HS) to sotalol (ie, those with the highest increase in QTc) and two individuals with the lowest sensitivity to sotalol (LS) to perform molecular and electrophysiological investigations. Results: At baseline, no differences in terms of repolarization durations, IKr amplitude, and ion channel expression were noted between the HS- and the LS-iPS-CM. However, the HS-iPS-CM displayed significant prolongation in action potential and field potential (FPD) durations after the application of 30 and 50μM of sotalol. They also displayed higher sensitivity to other drugs targeting hERG (E4031, vandetanib, and clarithromycin). Cavin1 mRNA and protein levels were increased by 2 fold in the HS-iPS-CM as compared to the LS-iPS-CM. Overexpressing Cavin1 in the LS-iPS-CM using adenovirus induced a higher sensitivity to sotalol as only 10μM was sufficient to induce 12% longer FPD. Consistently, the infection with Cavin1 increased the sensitivity of LS-CM to the other hERG blockers. In contrast, siRNA against Cavin1 reduced its expression by 60% in HS iPS-CM and switched their phenotype to a lower sensitivity to sotalol and the other hERG blockers. Interestingly, in line with the shortening of the FPD in LS-iPS-CM, overexpressing Cavin1 increased hERG expression in isolated membrane fraction from HEK cells stably expressing KCNH2. This suggests a role of Cavin1 in modulating hERG trafficking/recycling to the membrane and thereby the number of channels that can be blocked by drugs. Conclusion: Altogether, this work identified Cavin1 as a novel modulator of cardiomyocyte response to hERG blockers and a potential risk factor for diLQT. Further understanding of its contribution may pave the way for personalized drug prescription to avoid undesirable cardiotoxicity. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Leducq